PERBANDINGAN KARAKTERISTIK SPEKTRAL (SPECTRAL SIGNATURE) PARAMETER KUALITAS PERAIRAN PADA KANAL LANDSAT ETM+ DAN ENVISAT MERIS - Budhiman, Syarif (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
This study analyzed 3 optically active water constituents (Total Suspended Matter (TSM), Chlorophyll a (Chl a) and Color Dissolved Organic Matter (CDOM)) measured by in situ spectroradiometer (350-950 nm, interval 3.3 nm) and laboratory analysis for respective concentration measurements. Remote sensing reflectances ($R_s$) were derived from radiance and irradiance measurements and estimated using bio-optical model approach. The spectral signatures of derived $R_s$ were converted to ETM+ and MERIS bands using respective spectral response sensitivity. The converted $R_s$ were used to estimate the concentrations of 3 optically active water constituents using optimization method. The derived concentrations were validated with measured concentrations from laboratory analysis. ETM+ sensor with 4 bands provided better estimation for TSM ($R^2=0.70$) and CDOM ($R^2=0.64$) while the coefficient determination ($R^2$) for Chl a is only 0.46. However, MERIS sensor with 10 bands provided better estimation than ETM+, with coefficient determinations were higher than 0.70 for all water constituents. RMSE values for MERIS sensor showed smaller error estimation (16.84 gm-3 (TSM), 2.66 mg m-3 (Chl a) and 0.26 m-1 (CDOM)) compare with ETM+ sensor (19.89 gm-3 (TSM), 4.96 mg m-3 (Chl a) and 0.29 m-1 (CDOM)).